The influence of cognitive biases on investor decision-making: the moderating role of demographic factors - Yofy Syarkani; Erik Syawal Alghifari (Jurnal Siasat Bisnis, 2022)
Purpose – This study aims to see investor behavior in making investment decisions influenced by cognitive biases, namely overconfidence bias and the illusion of control bias by looking at the situational factors such as age, gender, and education. Design/methodology/approach – This study is conducted using a quantitative method by distributing a questionnaire. The questionnaires are measured using a 5-point Likert scale. The samples are taken from the population of individual investors in Bandung, West Java, with a number of 100 respondents. Findings – The results of this study prove that: (1) Illusion of control bias has an influence on investors’ decision-making, (2) Gender and education moderates the influence between the illusion of control bias on investor decision-making, (3) Age does not moderate the influence between the illusion of control bias on investor decision-making, (5) Overconfidence bias has an influence on investor decision-making, (6) Gender moderates the influence between overconfidence bias on investor decision-making, and (7) Age and education do not moderate the influence between overconfidence bias on investor decision-making. Research limitations/implications – The population in this study is limited to individual investors in Bandung. Future studies can conduct research in a similar direction using other populations, or focusing on a certain population, to ensure the generalizability of the results. Practical implications – Investors should be aware of cognitive biases while making decisions to invest. The biases can occur whether the investors realize it or not. Therefore, it would be useful for them to understand their cognitive biases so that investors can act rationally while making investment decisions. Originality/value – This study fills the research gap from the previous studies by examining the differences of investors' decision-making based on demographic factors, which are used as the moderating variables.